2010
DOI: 10.1128/aem.02475-09
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Fluorescent Dyes and Flow Cytometry To Quantify the Physiological State ofPichia pastorisduring the Production of Heterologous Proteins in High-Cell-Density Fed-Batch Cultures

Abstract: Matching both the construction of a recombinant strain and the process design with the characteristics of the target protein has the potential to significantly enhance bioprocess performance, robustness, and reproducibility. The factors affecting the physiological state of recombinant Pichia pastoris Mut ؉ (methanol utilization-positive) strains and their cell membranes were quantified at the individual cell level using a combination of staining with fluorescent dyes and flow cytometric enumeration. Cell vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 60 publications
1
42
0
1
Order By: Relevance
“…In addition, values of the growth characteristics (i.e. µ max , Y x/s , m s , see nomenclature given in Table 1) are crucial since they give a direct indication of whether the strain is physiologically impaired due to the introduction and expression of a foreign gene (Cos et al, 2006, Heyland et al, 2011, Hyka et al, 2010. Heavily impaired strains tend to stop growing, die and lyse, which causes problems in bioreactor operation because of heavy foaming as well as impaired product quality due to the release of host proteins or intracellular proteases (Jahic et al, 2003, Jahic et al, 2006, Zhou and Zhang, 2002.…”
Section: Biomass Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, values of the growth characteristics (i.e. µ max , Y x/s , m s , see nomenclature given in Table 1) are crucial since they give a direct indication of whether the strain is physiologically impaired due to the introduction and expression of a foreign gene (Cos et al, 2006, Heyland et al, 2011, Hyka et al, 2010. Heavily impaired strains tend to stop growing, die and lyse, which causes problems in bioreactor operation because of heavy foaming as well as impaired product quality due to the release of host proteins or intracellular proteases (Jahic et al, 2003, Jahic et al, 2006, Zhou and Zhang, 2002.…”
Section: Biomass Growthmentioning
confidence: 99%
“…Optimum conditions for the production of a recombinant protein in P. pastoris differ according to the target molecule and promoter (Hyka et al, 2010). To develop a production process for a newly constructed strain of unknown behaviour, it is therefore essential to start with its physiological characterisation.…”
Section: Characterisation Of Biomass Growth and Product Formationmentioning
confidence: 99%
“…34 This experimental approach also minimizes the effect of process conditions such as high agitation rate and oxygen enrichment, 35 that can lead to uncontrolled variables into the experimental design. Quadratic model was selected to analyze the ROL response surfaces.…”
Section: Surface Responses Of Rol Productionmentioning
confidence: 99%
“…Nevertheless, contrary to P GAP , P DeS can be still quite tightly regulated by the available carbon source type and level. Moreover, studies performed with another synthetic derepressed promoter P(De) revealed that there is a positive effect on cell physiology compared to expression under the control of P AOX1 (Hyka et al, 2010) which might also apply for P DeS .…”
Section: Discussionmentioning
confidence: 97%